Toxicity of Arsenic to Photobacterium phosphoreum, Daphnia magna, and Danio rerio at Different pH Levels. Issue 1 (30th November 2015) - He, Qun; Qu, Ruijuan; Wang, Xinghao; Wei, Zhongbo; Sun, Ping; Wang, Zunyao
Abstract : Although it has been widely known that arsenic poses great threat to organisms and arsenic species account for the toxic effect of the metalloid, relatively little attention has been given to the arsenic toxicity to different organisms at different pH values. Three kinds of aquatic organisms including Photobacterium phosphoreum, Daphnia magna, and Danio rerio were used to study the effects of pH on the toxicity of arsenic. Toxicity test results were analyzed by calculating EC50 values and for arsenic species at five different pH values (5.0, 6.0, 7.0, 8.0, and 9.0). As a result, As(III) is more toxic to the tested organisms than As(V), and P. phosphoreum was more sensitive to the toxicity of arsenic than D. magna and D. rerio . The toxicity of As(III) species is different for different organisms: dihydrogen arsenite, H2 AsO3 –, is more toxic to P. phosphoreum and D. rerio than arsenous acid, H3 AsO3, while H3 AsO3 is more toxic to D. magna . As for As(V), arsenate, HAsO4 2−, is the most toxic to P. phosphoreum, whereas dihydrogen arsenate, H2 AsO4 –, may be responsible for the toxicity to D. magna and D. rerio . As(III) and As(V) are more toxic to P. phosphoreum in an alkaline environment, while for D. magna in an acidic environment and As(III) is more toxic to D. rerio in an alkaline environment and As(V) in an acidic environment. Abstract : Arsenic, As(III) or As(V), at pH 5, 6, 7, 8, and 9, shows different toxicity to Photobacterium phosphoreum, Daphnia magna, and Danio rerio . H2 AsO3 − is more toxic to P. phosphoreum and D. rerio than H3 AsO3, and HAsO4 2− (As(V)) is the most toxic to P. phosphoreum . H2 AsO4 − may be responsible for the toxicity of arsenate to D. magna and D. rerio .